Evaluating the Effectiveness of Thailand’s Sor Por Kor Land Reform Policy - Yuthavong, Phenrat; Pinlaor, Annachhatre; Chakthranont, Bamrungsap; Chaudhury, Nuangchalerm (International Journal of Law and Public Policy (IJLAPP), 2025)
This article critically examines the effectiveness of Thailand’s Sor Por Kor (SPK) land reform policy from the perspective of agrarian law. Designed to allocate state lands to landless farmers, the SPK program has undergone recent reforms, including the conversion of land use rights into full land titles. While these changes aim to enhance tenure security and rural productivity, this article argues that the legal and institutional design of SPK remains vulnerable to elite capture, environmental degradation, and deviation from agrarian justice principles. Employing a normative-legal and socio-legal approach, this study evaluates SPK’s compliance with key agrarian law principles: distributive justice, the social function of property, sustainable land governance, and legal empowerment. The analysis reveals that while SPK has expanded access to land, its implementation suffers from weak regulatory oversight, fragmented legal frameworks, and contradictory development agendas. Recommendations are proposed to realign the SPK policy with the broader objectives of agrarian justice and food sovereignty in the context of emerging global land and food crises.